Closed-Loop Targeted Memory Reactivation during Sleep Improves Spatial Navigation - Shimizu, Renee E.; Connolly, Patrick M.; Cellini, Nicola; Armstrong, Diana M.; Hernandez, Lexus T.; Estrada, Rolando; Aguilar, Mario; Weisend, Michael P.; Mednick, Sara C.; Simons, Stephen B. (Frontiers in Human Neuroscience, 2018)
Sounds associated with newly learned information that are replayed during non-rapid eye movement (NREM) sleep can improve recall in simple tasks. The mechanism for this improvement is presumed to be reactivation of the newly learned memory during sleep when consolidation takes place. We have developed an EEG-based closed-loop system to precisely deliver sensory stimulation at the time of down-state to up-state transitions during NREM sleep. Here, we demonstrate that applying this technology to participants performing a realistic navigation task in virtual reality results in a significant improvement in navigation efficiency after sleep that is accompanied by increases in the spectral power especially in the fast (12-15 Hz) sleep spindle band. Our results show promise for the application of sleep-based interventions to drive improvement in real-world tasks.